The Role of Academics in Enhancing the Image and Digital Marketing of Traditional Podeng Cake – A Local Product of Tigaraksa, Tangerang Regency - Slamet Riyanto; Sinta Kurniaty Ratoko; Hendri Kartika Andri; Susilowati; Herru Sumerhu (The International Journal of Education Management and Sociology, 2025)
This community service program aims to strengthen the image and improve the digital marketing of Podeng cake, a traditional culinary product native to Tigaraksa, Tangerang Regency. Despite its unique taste and cultural value, Podeng cake has limited exposure and competitiveness in the modern marketplace. The program involved academics as key facilitators in empowering local producers through training in product development, branding, and digital promotion strategies. Activities included workshops on packaging design, storytelling for branding, and hands-on digital marketing sessions using social media and e-commerce platforms. The results showed a significant increase in the producers' understanding of market trends, improved product packaging, and enhanced online presence. Academics played a strategic role not only as knowledge providers but also as collaborators in transforming a local food product into a marketable brand. This initiative highlights the importance of university-community partnerships in preserving local heritage while promoting inclusive economic development.